Pengaruh Pertumbuhan Pakcoy (Brassica rapa l.) dengan Sistem Tanam Hidroponik Tipe Nutrient Film Technique (NFT) dan Media Kotoran Hewan (KOHE) - Elon Jipasca; Muhammad Rifqi Shodri; Ansori Rahman; Putri Wineni; Awalul Fatiqin; Thathit Suprayogi; Yahya Febrianto; Sudarman Rahman; Muafa Purwa Arsana; Rokiy Alfanaar (Universitas PGRI Silampari, 2024)
This study aims to assess the effect of planting media on pakchoi (Brassica rapa L.) growth. The research was conducted at Pak Slamet's Cipta Rasa Fruit Farm in October 2024. Each treatment used different planting media, with hydroponics supplemented with AB mix nutrients and KOHE without additional nutrients. The results showed that variations in growing media and nutrient supplementation had a significant impact on plant growth. The NFT hydroponic system gave the best results, with pakcoy reaching an average plant height (6.5 cm), number of leaves (8 leaves), and leaf width (5.8 cm) at 3-4 weeks after transplanting (HST) The results of plant height, number, and width of leaves from KOHE are listed. The provision of nutrients shows that the right amount and concentration can increase the overall growth of pakcoy.